Investigation of Air Quality in the Underground and Aboveground Multi-Storey Car Parks in Terms of Exhaust Emissions - DEMİR, ABDULLAH (ELSEVIER SCIENCE BV, 2015)
Exhaust emissions resulting from the motor vehicles have harmful and long lasting effects on both the human health and environment. Especially increasing concentrations of exhaust emissions in the closed environments and in the environments that cannot be sufficiently ventilated can cause damage on the human health and lead even to the death. The main harmful exhaust emissions based on the motor vehicles are gases such as CO (carbon dioxide), HC (hydrocarbons), and NOx (nitrogen oxides). In the circumstances of remaining under the influence of these gases, all the systems of the human body are generally get harmed. Therefore, the exhaust emission maps of the areas where there are the harmful exhaust emission concentrations in the high level, and the discharge methods of these gases in a very short space of time must be. In this study, the emission measurements have been carried out in four underground and five aboveground multi-storey car parks located in Istanbul. The effects on the human health of the measured fields were studied by the use of the results of the performed measurements, by comparing them with the maximum allowable concentration (MAC) and the threshold limit value-time weighed average (TLV-TWA) values. Taking into consideration all of the measurement results in the under-ground and above-ground multi-storey car parks, it is determined that the short-term use of the measured fields do not pose any risks in terms of human health. The suggestions regarding the improvement works of the car-parks were presented. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: air quality; exhaust emissions; forced ventilation; human health; multi-storey car park; VENTILATION; GARAGE